Dominance of Government Communication Messages in The Implementation of The Bengkulu Tabut Festival 2025 - Alfarabi; Nadya Sukmawati Dewi; Heni Indriani; Bintara Santika; Prio Santoso; Puji Haryadi Mulyana Sukma (DAWUH : Islamic Communication Journal, 2026)
This study aims to analyze the dominance of government communication messages in the implementation of the Bengkulu Tabut Festival 2025 and to examine how the meaning of the Tabut tradition is represented within the context of cultural tourism. This research employs a critical paradigm with a qualitative approach. Data were collected through in-depth interviews and document analysis involving informants from the Bengkulu Provincial Tourism Office, the event organizer Areacorps Creative, and traditional communities such as Balai Adat Rajo Penghulu and the Kerukunan Keluarga Tabut (KKT). Data analysis was conducted using the interactive model of Miles and Huberman.The results show that the local government acts as a dominant actor in shaping and constructing the meaning of Tabut through various representations within the festival, such as cultural performances, public service programs, and community economic activities. From the perspective of Muted Group Theory, this condition indicates an imbalance in the production of meaning, where the government as the dominant group controls the public narrative, while the Kerukunan Keluarga Tabut (KKT) occupies a less dominant position in determining the meaning of the tradition. Nevertheless, the Kerukunan Keluarga Tabut (KKT) demonstrates forms of resistance by maintaining the sacred values of Tabut as a spiritual cultural heritage.